HUBUNGAN ANTARA KETERAMPILAN MENYIMAK INFORMASI DENGAN BERBICARA MENYAMPAIKAN KESIMPULAN INFORMASI PADA SISWA KELAS III SDN 20 BANYUASIN III - Youhana Lorenza; Hetilaniar; Adrianus Dedy (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Language skills consist of 2 (two) categories: written and spoken skills. Students with good listening skills can increase their thinking power and make their speaking skills good so that teaching and learning activities become active and learning objectives can be achieved. However, in reality, the learning process that occurred during this pandemic did not improve the students' skills because students were required to understand the material and do the assignments independently at home. It means that students' listening and speaking skills were not trained. Based on this, the problem in this study was to see a relationship between listening to information skills and speaking for conveying the information conclusions of the third-grade students at SDN 20 Banyuasin III. This study aimed to determine the relationship between the students' listening and speaking skills. The method used in this study was a correlational method with a quantitative research approach. The results showed that the students' ability to listen to information was strongly correlated to their speaking for conveying information conclusions skills. It was seen from the data obtained from the Pearson product-moment correlation formula, which found that rcount = 0.894.